Development Of Amino-functionalized Magnetic Silica Nanocomposite For The Magnetic Solid-phase Extraction Of Β-lactam Antibiotics In Milk - Halim, Wan Ibrahim Thani Abd (2023)
This study describes a magnetic solid-phase extraction (MSPE) method based on (3-aminopropyl)triethoxysilane (APTES) functionalized magnetic silica nanocomposites (MSN) for the determination of four β-lactam antibiotics (BLAs) namely oxacillin (OXA), cloxacillin (CLO), dicloxacillin (DIC), and nafcillin (NAF) in milk samples prior to high performance liquid chromatography with diode array detector (HPLC-DAD) analysis. The chemical structure and surface morphology of APTES-MSN were analyzed and characterized by Fourier transform infrared (FTIR) spectroscopy, Brunauer-Emmett-Teller (BET) surface area analyzer, x-ray diffraction (XRD), thermogravimetric analysis (TGA), transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), and vibrating sample magnetometer (VSM). Several essential parameters affecting the extraction efficiency were studied, such as sample pH, amount of sorbent, extraction time, type of desorption solvent, desorption time, volume of desorption solvent, volume of sample, and salt addition. The developed APTES-MSN-MSPE method provided good linearity range from 5 to 500 μg L-1 for OXA, CLO, DIC, and NAF with good coefficient of determination (R2 = 0.9987 - 0.9998), low limits of detection (0.26 -1.00 μg L-1), acceptable RSD% (n = 3) (1.59% – 5.00%) and satisfactory relative recoveries (93.43% – 113.42%). The APTES-MSN- MSPE combined with HPLC-DAD was successfully employed for the analysis of targeted BLAs in 15 selected milk samples, and the presence of studied analytes was quantified in 4 samples.